What is a good midwife? Insights from the literature - Borrelli, Sara E. (Elsevier, 2014)
OBJECTIVE: to review the literature around what is considered to be a good midwife and in particular what women value in a midwife, in order to identify the gaps in the evidence for future research. DESIGN: this paper reviews the research in the area of interest over the past 30 years. The literature search focused on the concept of good midwife using synonyms and antonyms. The inclusion criteria included language (English or Italian). The examined databases were Medline, Maternity and Infant Care, Applied Social Sciences Index and Abstract and CINAHL. SETTING: studies conducted in high-income countries were taken into account. A focused review of papers which explicitly investigated what a good midwife means and a thematic analysis on what women value in a midwife were carried out. PARTICIPANTS: different standpoints have been considered (midwives, student midwives, women and their partners), focusing in particular on women viewpoint. FINDINGS: the literature review reveals information about what is considered to be a good midwife from a range of perspectives and what women value in a midwife. A good midwife should possess several attributes: theoretical knowledge, professional competencies, personal qualities, communication skills and moral/ethical values. According to the thematic analysis around what childbearing women value in a midwife, frequent key-themes emerging from the literature were: support, possibility of choice, feeling in control and having appropriate information. KEY CONCLUSIONS: the meaning of good midwife might change according to different actors involved in midwifery care and there is no agreement on the definition of what constitutes a good midwife. Furthermore, it is not clear if what women value in a good midwife corresponds to the midwives' perception of themselves as good professionals. There is a dearth of information around women's expectations and experiences specifically of a good midwife, and even less around whether this changes according to where they give birth. IMPLICATIONS FOR PRACTICE: this literature review seeks to stimulate debate and reflection among midwives and professionals involved in the childbearing event, in order to fulfil women's expectations of their midwife and increase their satisfaction with the birth experience. The identification of the gaps in the evidence provided the starting point and allowed the development of research questions and methodology for an ongoing doctoral research. On the basis of the gaps in the evidence, the doctoral research will explore and seek to explain nulliparous women's expectations and experiences of a good midwife in the context of different planned place of birth, using a Grounded Theory methodology. It is also expected that the findings of this literature review will stimulate additional research in this area to ultimately inform midwifery practice and midwifery educational programmes.